Toxoplasma gondii ROP18I inhibits host innate immunity through cGAS‐STING signaling. Issue 2 (27th January 2022) - Chen, Min; Yao, Lijie; Zhou, Lijuan; Yang, Pei; Zou, Weihao; Xu, Liqing; Li, Shengmin; Peng, Hongjuan
Abstract: Toxoplasma gondii is an opportunistic protozoan, which widely infects humans and other warm‐blooded animals. The type I interferon (IFN) such as IFN‐α/β is involved in cGAS‐STING signaling to resist T . gondii infection. We found in RAW264.7 cells, that T . gondii virulence factor Tg ROP18I, inhibited IFN‐β production through interacting with interferon regulatory factor 3 (IRF3). Besides, Tg ROP18I interacted with p62 and Tumor Necrotic Factor Receptor Associated Factor 6 (TRAF6), which resulted in the inhibition of TRAF6‐p62 interaction, and phosphorylation of p62. Furthermore, Tg ROP18I restricted the recruitment of ubiquitin, p62 and microtubule‐associated protein light chain 3 (LC3) to the parasitophorous vacuole membrane (PVM) in IFN‐γ‐stimulated murine cell line L929 cells. In IFN‐γ‐stimulated human cells, Tg ROP18I restricted the decoration of PVM with ubiquitin, p62, and LC3, and bound with TRAF2, TRAF6, and p62, respectively. As a result, Tg ROP18I led to a successful parasitic replication in murine and human cells. Collectively, our study revealed the function of Tg ROP18I in suppressing host type I interferon responses in T . gondii infection for parasitic immune escape.